The usborne big book of rockets and spacecraft - Stowell, Louie (London: Usborne Publishing, 2015)
Providing a fascinating insight into the world of space travel, this big book features a wide range of spaceships, shuttles, rockets, satellites and the International Space Station. With four huge, fold-out pages which allow children to marvel as the scale of outer space and see in detail the complexity of these marvels of science and engineering
Keywords: Astronautics -- Astronautics Juvenile literature -- Juvenile works